2004
DOI: 10.1007/s11743-004-0325-7
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and surface properties of phenylalanine‐glycerol ether surfactants

Abstract: A novel homologous series of 1-N-L-phenylalanine-glycerol ether surfactants was synthesized in satisfactory yields via reaction of epichlorohydrin with aliphatic alcohols with alkyl chains of 10-15 carbon atoms. Structural assignment of the new compounds was made on the basis of elemental analysis and spectroscopic data. Critical micelle concentration (CMC), surface tension at the CMC (γ CMC ), surfactant concentration required to reduce the surface tension of the solvent by 20 mN/m (pC 20 ), and the interfaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 14 publications
2
34
1
2
Order By: Relevance
“…It was suggested that the amino acid surfactants exhibited antimicrobial activities when they were in monomeric form but not in micellar form . Varka et al studied the amino acid‐based surfactants synthesis, characterization and surface properties like CMC, SFT, excess and minimum surface area. The linearity trend, a regular decreasing order with an increase in the number of methylene groups in alkyl chain was observed in all anionic, cationic, and nonionic surfactants .…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that the amino acid surfactants exhibited antimicrobial activities when they were in monomeric form but not in micellar form . Varka et al studied the amino acid‐based surfactants synthesis, characterization and surface properties like CMC, SFT, excess and minimum surface area. The linearity trend, a regular decreasing order with an increase in the number of methylene groups in alkyl chain was observed in all anionic, cationic, and nonionic surfactants .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, less hydrophilic molecules will be moved in the direction of the non-polar phase-the air; hence, their improved effectiveness in reducing surface tension. This is typical to various series of ionic and nonionic [32][33][34][35][36] surfactants. Better surface active properties have been described for a naturally produced lipopeptide surfactant-surfactin.…”
Section: Resultsmentioning
confidence: 95%
“…The highest value (pC 20 = 3.95) was observed for Palm-KG-NH 2 , while the lowest (pC 20 = 1.81) was noted for Myr-KKKK-NH 2 . This means that tested lipopeptides with smaller hydrophilic heads and longer hydrophobic tails have better ability to adsorb at the water/air interface, which is characteristic of all types of surface active agents [32][33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…However, an extensive investigation of the wetting agents' role has not been done until now. The aim of the present work is the study of the hot mercerization of cotton under tension by using nonconventional surfactants (Scheme ) as wetting agents 23, 24. The new compounds have many properties required for mercerization such as their solubility in alkaline media without decomposition of the molecule, due to the stable ether bond between the glycerol moiety and the alkyl chain, in contrast to the hydrolysable ester bond of the conventional surfactants, absence of affinity to the cellulose fiber, and efficiency at low concentrations 25…”
Section: Introductionmentioning
confidence: 99%